Enhanced pseudonym based key agreement algorithm for near feild communication (NFC) - Abu-Baker Alkalaaf, Howida (2014)
Nowadays, near field communication (NFC) has been implemented in many fields such as ticketing, public transport payment, credit cards and Wireless Local Area Network (WLAN) set up. In the near future, NFC is expected to replace credit cards in the electronic payment. Therefore, a security issue in NFC has become a crucial issue to be resolved. One of the critical security issues in NFC is key agreement. The weakness of current key agreement makes user privacy vulnerable to attack. To address that issue, this research proposes an enhanced algorithm to protect the user privacy in the NFC. The enhanced algorithm extends pseudonyms algorithm which has been implemented for resolving privacy protection problems in Vehicular ad hoc networks (VANETs). The experimental results show that the proposed algorithm is effective to protect user privacy due to random public key generation. Moreover, the pseudonym has acceptable latency in generating and processing key agreement. The latency of the proposed algorithm is 2% lower than the traditional Diffie-Hellman key agreement algorithm. That capability makes pseudonym suitable to be used with devices of limited resources like NFC devices